2008
DOI: 10.1038/npp.2008.75
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive Effect of Midazolam on Fear Memory Reconsolidation: Decisive Influence of Reactivation Time Span and Memory Age

Abstract: Benzodiazepine (BDZ) administered shortly after retrieval disrupts the reconsolidation of fear memory. In this research, we explored the way in which different factors that limit the emergence of such process may affect BDZ's disruptive effect on fear memory reconsolidation. Animals were conditioned in a contextual fear paradigm; the consolidated memory was reactivated by exposure to the associated context for different periods of time that were followed by midazolam (MDZ) administration. We also studied MDZ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
131
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(151 citation statements)
references
References 54 publications
19
131
1
Order By: Relevance
“…This was due to the SAL group expressing increased freezing from test to retest (P , 0.01; Cohen's f ¼ 3.71) suggesting spontaneous recovery, which is consistent with the typical pattern of extinction learning (Bouton 2004). The MDZ group, however, showed intact CR expression, a consequence of the amnesic agent over the consolidation of extinction memory, as previously reported with MDZ (Bustos et al 2009) hypothermia (Briggs and Riccio 2007), and other pharmacological agents (Eiserberg et al 2003;Pedreira and Maldonado 2003;Suzuki et al 2004). Figure 7A shows the course of extinction minute by minute over the 15 min of reactivation time.…”
Section: Methodssupporting
confidence: 56%
See 3 more Smart Citations
“…This was due to the SAL group expressing increased freezing from test to retest (P , 0.01; Cohen's f ¼ 3.71) suggesting spontaneous recovery, which is consistent with the typical pattern of extinction learning (Bouton 2004). The MDZ group, however, showed intact CR expression, a consequence of the amnesic agent over the consolidation of extinction memory, as previously reported with MDZ (Bustos et al 2009) hypothermia (Briggs and Riccio 2007), and other pharmacological agents (Eiserberg et al 2003;Pedreira and Maldonado 2003;Suzuki et al 2004). Figure 7A shows the course of extinction minute by minute over the 15 min of reactivation time.…”
Section: Methodssupporting
confidence: 56%
“…When reviewing the literature to better understand these seemingly contradictory outcomes, a pattern is seen: for example, Pedreira and Maldonado (2003) (also see Eisenberg et al 2003) observed that reactivation duration influences in part which process takes place. This pattern has been replicated by other groups that further found that short presentations only produce memory retrieval, intermediate reactivations destabilize the memory and long reactivations generate extinction learning (Suzuki et al 2004;Bustos et al 2009;Piñeyro et al 2013).…”
supporting
confidence: 65%
See 2 more Smart Citations
“…Moreover, there are boundary conditions that place constraints on the onset of both the labile phase and the re-stabilization process (Tronson and Taylor, 2007). For instance, memory age, the duration of the reactivation period, and the interaction between these two factors have a decisive influence on the susceptibility to disruption after memory reactivation (Bustos et al, 2009;Suzuki et al, 2004). As memory ages, it is more difficult to induce post-retrieval retrograde amnesia by pharmacological intervention as compared with newer memories (Frankland et al, 2006;Milekic and Alberini, 2002;Suzuki et al, 2004).…”
Section: Introductionmentioning
confidence: 99%